Antioxidant activity and formulation evaluation of Morinda citrifolia L.leaf ethanol extract nanoparticles incorporated into moisturizing gel - Eriska Agustin; Ranti Ayu Anjelina; Yola Yernianti (Universitas Mataram, 2026)
Skin is continuously exposed to environmental stressors such as ultraviolet radiation and pollution, which trigger the formation of reactive oxygen species (ROS) leading to oxidative stress, premature aging, and skin damage. Therefore, the development of topical antioxidant formulations from natural sources has become increasingly important. This study aimed to develop nanoparticles of Morinda citrifolia L. leaf ethanol extract and incorporate them into a moisturizing gel, followed by evaluation of their physicochemical properties and antioxidant activity. The extract was prepared by maceration using 96% ethanol, while nanoparticles were synthesized using the ionic gelation method with chitosan and sodium tripolyphosphate. Particle size, polydispersity index, morphology, and antioxidant activity (DPPH method) were evaluated. The nanoparticles exhibited sizes below 200 nm with a uniform distribution (PDI< 0.3). The optimized formulation showed the smallest particle size (FIII=77.5±6.36 nm) and good stability. Antioxidant activity increased after nanoparticle formulation, with IC₅₀ values decreasing from 182.4±2.26 ppm (extract) to 145.4±6.89 ppm (FIII), indicating moderate activity. The gel formulations showed good physical stability and acceptable viscosity, although pH values were below the ideal skin range. The moisturizing test demonstrated significant improvement in skin hydration. In conclusion, nanoparticle incorporation enhanced antioxidant and moisturizing performance, indicating potential for topical applications.